1995
DOI: 10.1177/107110079501600805
|View full text |Cite
|
Sign up to set email alerts
|

Silastic Single-Stem Implants in the Treatment of Hallux Rigidus

Abstract: Forty cases of hallux rigidus treated by Silastic hemiarthroplasty over an average period of 110 months have been reviewed here. As many as 36% (14 feet) of the patients were unhappy with the results of their operation. Six implants had to be removed because of increasing pain and fragmentation of the prosthesis. These patients improved after the prosthesis was removed. It is concluded that Silastic hemiarthroplasty does not give an acceptable level of good results when compared with published reports of other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Following arthrodesis of the MTP joint, metatarsalgia was reported in 23%, 13 following silicone hemiarthoplasty in 25% of patients. 37 Pedobarographic assessment demonstrated a decrease of maximum pressure, force and contact area under the great toe. This decrease in pedobarographic function was surprisingly moderate.…”
Section: Discussionmentioning
confidence: 99%
“…Following arthrodesis of the MTP joint, metatarsalgia was reported in 23%, 13 following silicone hemiarthoplasty in 25% of patients. 37 Pedobarographic assessment demonstrated a decrease of maximum pressure, force and contact area under the great toe. This decrease in pedobarographic function was surprisingly moderate.…”
Section: Discussionmentioning
confidence: 99%
“…This precipitates a synovitic process within the joint [19] that ultimately leads to fragmentation of the prosthesis and periimplant osteolysis. When this eminently predictable process occurs, patients represent to clinic complaining of pain at the site of the arthroplasty [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…In studies to evaluate the results of these prostheses (Silastic ® ), we found wide variability in the conclusions, ranging from long-term success (13,14) to early failure. Shankar (5) , in 1995, presented a trial involving 40 patients with an average follow-up period of 110 months, in which the complication rate was 36%, mainly due to fragmentation of the silicone. A high incidence of granulomatous reactions to silicone particles is also reported in about 72% of patients, and causes significant osteolysis (6,7) .…”
Section: Discussionmentioning
confidence: 99%
“…In 1979, Swanson proposed the use of the interposition silicone prosthesis (Silastic ® ) (4) . However, these prostheses presented several complications, including fracture of the prosthesis and synovitis and bone lysis related to worn particles of silicone (5)(6)(7) . In 1994, the use of zirconium ceramic components (Moje ® ) was tested, but these materials also presented several complications, particularly due to fracture of the material (2,8,and 9) .…”
Section: Introductionmentioning
confidence: 99%